2017
DOI: 10.1016/j.bbr.2017.05.063
|View full text |Cite|
|
Sign up to set email alerts
|

Prodepressant- and anxiogenic-like effects of serotonin-selective, but not noradrenaline-selective, antidepressant agents in mice lacking α2-containing GABAA receptors

Abstract: Deficits in neuronal inhibition via gamma-aminobutyric acid (GABA) type A receptors (GABAA-Rs) are implicated in the pathophysiology of major depressive disorder and the therapeutic effects of current antidepressant treatments, however, the relevant GABAA-R subtype as defined by its alpha subunit is still unknown. We previously reported anxiety- and depressive-like behavior in alpha2+/− and alpha2−/− mice, respectively (Vollenweider, 2011). We sought to determine whether this phenotype could be reversed by chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In this same study, subchronic treatment with desipramine had no effect ( Shen et al, 2010 ), suggesting that this drug acts over time to balance GABAergic inhibition deficits. In another study, chronic fluoxetine treatment induced pro-depressive and anxiogenic-like effects in γ2+/- mice ( Benham et al, 2017 ), pointing to a requirement of GABA A -containing γ2 subunit in the antidepressant effect of SSRIs. Interestingly, studies reported that fluoxetine can act directly as an allosteric modulator of GABA A receptors ( Robinson et al, 2003 ).…”
Section: The Gabaergic System As a Therapeutic Target For The Treatmementioning
confidence: 96%
“…In this same study, subchronic treatment with desipramine had no effect ( Shen et al, 2010 ), suggesting that this drug acts over time to balance GABAergic inhibition deficits. In another study, chronic fluoxetine treatment induced pro-depressive and anxiogenic-like effects in γ2+/- mice ( Benham et al, 2017 ), pointing to a requirement of GABA A -containing γ2 subunit in the antidepressant effect of SSRIs. Interestingly, studies reported that fluoxetine can act directly as an allosteric modulator of GABA A receptors ( Robinson et al, 2003 ).…”
Section: The Gabaergic System As a Therapeutic Target For The Treatmementioning
confidence: 96%
“…Global heterozygous knockdown of the γ2 subunit leads to impaired GABAergic signaling [11 ], as well as anxiety- and despair-like behavior that is reversed with chronic desipramine (but not fluoxetine) [127] and acute ketamine [126] treatment. More recently it was demonstrated that global knockdown of the α2 subunit also leads to anxiety- and despair-like behavior [9], and that in these mice sensitivity to anxiogenic-and prodepressant-like effects with chronic fluoxetine treatment is increased [128]. Studies in post-partum female mice demonstrated that decreases in the δ subunit lead to increased anxious- and depressive-like behavior as well as maternal neglect, while the δ subunit preferring agonist gaboxadol improved maternal care [129].…”
Section: Gabaa Receptors In Stress and Depression Circuitsmentioning
confidence: 99%
“…Consequently, such mice may provide an insight into how genetic variations and the environment interact to perturb brain circuitry, thereby predisposing to substance abuse, but also to influence other psychological disorders such as anxiety and depression. ( Low et al, 2000 , Dixon et al, 2008 , Benham et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%